Stad as A Strategy of Teaching Reading Comprehension in Junior High School - Ferina, Fitri (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2015)
This research investigated whether there was a significant difference on students’ achievement in reading comprehension taught using STAD and lecture method. The sample was the eighth-graders of SMPN 3 Banjarmasin. A quasi-experimental design was employed in this research. The experimental group was taught using STAD while control group was taught using lecture method. A reading comprehension test as the instrument of collecting data was administered for both groups. Based on the research result using t-test, it was found that the t value was higher than t-table (2.39315 > 2.00) which means that there is a significant difference of achievement between the experimental group and control group. From these findings it can be interpreted that the use of STAD is more effective than lecture method in teaching reading comprehension for junior high school students. It is suggested for English teachers in Junior High School to use STAD in teaching reading since it is useful in improving students’ reading comprehension achievement.